STRUCTURAL ELUCIDATION OF TRANSITION METAL COMPLEXES OF MODIFIED DIAMINE ALONGWITH BIOASSAY STUDIES - Rehman, S. U.; Noreen, S.; Rashida, Miss.; Akram, M.; Ali, K.; Ahmad, I.; Arshad, M.; Bukhari, I. H. (The Nucleus, 2020)
A number of complexes of modified diamine (3,7-dimethyl-1,5-dithia-3,7-diazacyclooctane), were prepared with first row divalent transition metals, i.e., Cu(II) and Zn(II). The structures of these complexes were elucidated on the basis of various physical techniques such as mass spectrometry, NMR, IR, UV-Visible spectroscopies, magnetic and conductance measurements. Bioassay of these complexes has also been carried out. The physical measurements confirm distorted tetrahedral structure for these complexes.